Does the spillage of petroleum products in anopheles breeding sites have an impact on the pyrethroid resistance? (2007)
Background: The emergence of Anopheles populations capable of withstanding lethal doses of insecticides has weakened the efficacy of most insecticide based strategies of vector control and, has highlighted the need for further studies on the mechanisms of insecticide resistance and the various factors selecting resistant populations of mosquitoes. This research targeted the analysis of breeding sites and the oviposition behaviour of susceptible and resistant populations of Anopheles in localities of spilled petroleum products. The aim was to establish the possible contribution of oil spillage in the selection of pyrethroid resistance in malaria vectors. Methods: Anopheles breeding sites were identified and the insecticide susceptibility of the Anopheles gambiae populations mapped in 15 localities of South Western Nigeria. The presence of oil particles as well as the turbidity, the dissolved oxygen and the pH of each identified breeding site was recorded. Data were cross-analysed to correlate the habitat types and the insecticide susceptibility status of emerging mosquitoes. The second phase of this study was basically a laboratory model to provide more information on the implication of the spillage of petroleum on the selection of pyrethroid resistance in An. gambiae. Results: Moderate levels of resistance following exposure to permethrin-impregnated papers were recorded with the majority of An. gambiae samples collected in the South Western Nigeria. Data from this study established a link between the constituency of the breeding sites and the resistance status of the emerging Anopheles. Conclusion: This study has revealed the segregational occupation of breeding habitats by pyrethroid resistant and susceptible strains of An. gambiae in south-western Nigeria. Compiled results from field and laboratory research point out clear relationships between oil spillage and pyrethroid resistance in malaria vectors. The identification of this factor of resistance could serve as strong information in the management of insecticide resistance in some West African settings.